2016
DOI: 10.1111/maps.12639
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of H2O in the Martian interior: Implications for the abundance of H2O in depleted and enriched mantle sources

Abstract: Abstract-We conducted a petrologic study of apatite within 12 Martian meteorites, including 11 shergottites and one basaltic regolith breccia. These data were combined with previously published data to gain a better understanding of the abundance and distribution of volatiles in the Martian interior. Apatites in individual Martian meteorites span a wide range of compositions, indicating they did not form by equilibrium crystallization. In fact, the intrasample variation in apatite is best described by either f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
178
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(192 citation statements)
references
References 205 publications
(294 reference statements)
12
178
2
Order By: Relevance
“…The magma source for Martian basalts is the Martian mantle; thus, the basaltic phosphates provide information on the Martian mantle composition as well as its evolution in the course of melting progression [11,[18][19][20][21]. Volatile-bearing apatite (Ca 10 (PO 4 ) 6 (Cl, F, OH) 2 ), volatile-free merrillite (Ca 18 Na 2 Mg 2 (PO 4 ) 14 ) and the high-pressure phase tuite (γ-Ca 3 (PO 4 ) 2 ) are frequently observed in extra-terrestrial bodies ( [1,3,5,6,12,[22][23][24][25] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The magma source for Martian basalts is the Martian mantle; thus, the basaltic phosphates provide information on the Martian mantle composition as well as its evolution in the course of melting progression [11,[18][19][20][21]. Volatile-bearing apatite (Ca 10 (PO 4 ) 6 (Cl, F, OH) 2 ), volatile-free merrillite (Ca 18 Na 2 Mg 2 (PO 4 ) 14 ) and the high-pressure phase tuite (γ-Ca 3 (PO 4 ) 2 ) are frequently observed in extra-terrestrial bodies ( [1,3,5,6,12,[22][23][24][25] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NWA 6234 recorded that merrillite reacted with an OH-Cl-F-rich melt to form apatite [55]. Shergottites contain trace quantities of apatite that is relatively more abundant in the enriched ones compared to their depleted counterparts [46]. It has been observed that all phosphate grains present in SaU 094 and SaU 150 meteorites, paired with SaU 005/008, represent merrillite, and no apatite has been found [69,101].…”
Section: Petrogenetic Relationshipmentioning
confidence: 97%
“…Furthermore, it is envisaged that water in the Martian mantle is heterogeneously distributed based on the estimates from the SNCs (i.e., 14-250 ppm; [46]. However, depleted shergottite mantle source is relatively water-poor (i.e., 14-23 ppm; [46]) compared to the enriched ones (i.e., 36-73 ppm; [46]). Mantle derived water that exhumed on the Martian surface in large fluxes during the earlier history of Mars (Noachian to early Hesperian periods; [23]), has been followed by further water contributions from shergottite-like magmatism during the Amazonian era [23].…”
Section: Petrogenetic Relationshipmentioning
confidence: 99%
See 2 more Smart Citations